INTEGRATED ELECTRICAL CONTROL PANELS USING JAVA PROGRAMING - Suprapto Suprapto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2005)
Technology trend nowadays is connecting one instrument with itothers to be an integrated system that can ease human's work.Integrated Control Panel is an electricity control panel which is controlled remotely. This control panel is so much because of its efficiency which is gained and more than one instrument which are controlled. This control panel is a remote controlled that can ease human's work, do security control and self control. This research a . started from software and hardware plan making and implementing the result of the analytic technique is used to answer whether theresearch on remote sensing using Web can be more efficient and makehuman's work easier. The result of the analytic technique is shown bythe speed of access time between the client and the server. From thefinding it can be conclude that Integrated Control Panel which can be controlled through web browser can be ease human's work in doingcontrol access to electricity instruments. This control method isobviously more efficient because of small access time. This is shown by the mean of access time which is only 265 milliseconds. This panelis provide with database system to save data control. This databasecan be accessed to know the data control.